ChemInform Abstract: Catalytic Activity and Antibacterial Properties of Nanopolymer‐Supported Copper Complex for C—N Coupling Reactions of Amines and Nitrogen‐Containing Heterocycles with Aryl Halides. Issue 1 (17th December 2015) - Nasrollahzadeh, Mahmoud; Zahraei, Ali; Pourbasheer, Eslam
Abstract: Efficient N‐arylation of N‐heterocycles and amines with aryl halides is achieved using a novel nanopolystyrene‐anchored Cu(II) tetrazole complex as stable heterogeneous catalyst.